DBU-Mediated Dimerization: Facile Access to 9,9′-Bifluorenylidenes and Isoindigos - Purahong N. (2023)
The present work describes 1,8-diazabicyclo[5.4.0]-7-undecene (DBU)-promoted self-dimerization of 9-chlorofluorenes and 3-chlorooxindoles for the production of the respective 9,9′-bifluorenylidene and isoindigo derivatives in moderate to good yields (29-97% yield). The reaction readily proceeded under mild and metal-free conditions with short reaction time. A scale-up synthesis (5.0 mmol) of some selected 9,9′-bifluorenylidene derivatives in decent yields highlights the synthetic utility of the reported protocol.